2015
DOI: 10.4111/kju.2015.56.5.337
|View full text |Cite
|
Sign up to set email alerts
|

Current role of multiparametric magnetic resonance imaging in the management of prostate cancer

Abstract: The purpose of this review was to evaluate the current role of multiparametric magnetic resonance imaging (mp-MRI) in the management of prostate cancer (PC). The diagnosis of PC remains controversial owing to overdetection of indolent disease, which leads to overtreatment and subsequent patient harm. mp-MRI has the potential to equilibrate the imbalance between detection and treatment. The limitation of the data for analysis with this new technology is problematic, however. This issue has been compounded by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Inspired by their studies, we performed an analysis on the whole gland, which contained both information on the tumor and its surroundings . The gland segmentation can avoid the mismatching phenomenon and inaccurate segmentation caused by image deformation between T 2 WI and DWI . Meanwhile, the gland segmentation is easier to achieve than the segmentation of tumor zone, which may also support the application of automatic or semiautomatic segmentation …”
Section: Discussionmentioning
confidence: 99%
“…Inspired by their studies, we performed an analysis on the whole gland, which contained both information on the tumor and its surroundings . The gland segmentation can avoid the mismatching phenomenon and inaccurate segmentation caused by image deformation between T 2 WI and DWI . Meanwhile, the gland segmentation is easier to achieve than the segmentation of tumor zone, which may also support the application of automatic or semiautomatic segmentation …”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing percentage of other diagnostic tools in 2013 suggest that more advanced diagnostic and investigation/staging techniques such as transperineal prostate biopsy [ 29 ] or multiparametric magnetic resonance (mMRI), that are becoming more widely used in Australia. mMRI is emerging as a useful tool in the investigation and treatment of PCa, by identifying regions which may represent clinically significant PCa [ 30 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of current literature supporting utility of multi-parametric MRI (mpMRI) showed the sensitivity of mpMRI for PCa detection to be 80–90% and the specificity for suspicious lesion to be between 50% and 90%16. Despite a growing body of literature, debate over capability of mpMRI in reliably detecting significant cancer still remains17. Others have advocated saturation biopsies to enhance cancer detection rate.…”
Section: Discussionmentioning
confidence: 99%